VALUATION OF PHYSICAL ACTIVITY IN SCHOOL TEENAGERS, BETWEEN 10 AND 18 YEARS OLD, IN EDUCATIONAL ESTABLISHMENTS OF THREE CITIES IN THE REGION OF MAULE, CHILE (Fiep Bulletin - online, 2016)
The practice of physical activity is a recognized factor for maintenance and health care. The inclusion of these activities in the daily life of teenagers depends on the level of valuation that they deliver to physical activity. The objective of this study was to verify the valuation that teenagers from 10 to 18 years old, deliver to physical activity in educational establishments of the Regióndel Maule, Chile. Methodology: quantitative study, descriptive; application of Valuation Questionnaire of Physical Activity; four establishments in the three Chilean administrative dependencies; sample of 1245 subjects; results presented in frequency descriptive statistics. Results: 65% of the sample to value physical activity (between 61 and 80% of the maximum score of valuation); men have a higher valuation of physical activity than women. Conclusions: the sample give value to physical education activity; but analysis suggests that the valuation isn't directly related to realization of physical activity.
Keywords: physical activity; valuation; teenagers.